Stories of Love from Vikings to Tinder The Evolution of Modern Mating Ideologies, Dating Dysfunction, and Demographic Collapse - Larsen, Mads (Oxford Taylor & Francis, 2024)
Increasing levels of singledom, dating dysfunction, and sexual inactivity contribute to plummeting fertility rates. This book investigates the perhaps most foundational factor behind this uncoupling: our present era$1 (Bs ideology of love. Throughout human history, communities have shared fictional stories infused with various mating moralities that compel people to pair-bond and reproduce. After taking readers on a 6-million-year journey through hominin mating regimes$1 (Bwith various extents of promiscuity, polygyny, and monogamy$1 (BStories of Love from Vikings to Tinder investigates the past millennium's radical evolution of Western mating beliefs. Nordic literary works illuminate the pivotal transitions between the West$1 (Bs First, Second, and Third Sexual Revolutions, which occurred around the years 1200, 1750, and 1968. The conclusion chapter points to the Fourth Sexual Revolution, symbolically placed in 2029. Artificial intelligence and other technologies seem likely to transform our mating practices more radically than any of the previous revolutions.s
English
Keywords: Philosophy: aesthetics; Sociology; Literary studies: general; Western Love; Romantic relationships; Sexual Revolution; Family; Marriage; storytelling; Icelandic Sagas